2016
DOI: 10.3402/qhw.v11.30563
|View full text |Cite
|
Sign up to set email alerts
|

Shared decision-making in mental health care—A user perspective on decisional needs in community-based services

Abstract: BackgroundShared decision-making (SDM) is an emergent research topic in the field of mental health care and is considered to be a central component of a recovery-oriented system. Despite the evidence suggesting the benefits of this change in the power relationship between users and practitioners, the method has not been widely implemented in clinical practice.ObjectiveThe objective of this study was to investigate decisional and information needs among users with mental illness as a prerequisite for the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 18 publications
1
75
0
Order By: Relevance
“…Most importantly, perhaps, focus group members referred to the importance of individuality and the need to treat it as part of the recovery journey where they are themselves an expert. Grim et al (2016) also found that service users felt it extremely important to prepare for meetings by considering what experiential knowledge to share at the meeting.…”
Section: Factors Related To the Service Usermentioning
confidence: 99%
“…Most importantly, perhaps, focus group members referred to the importance of individuality and the need to treat it as part of the recovery journey where they are themselves an expert. Grim et al (2016) also found that service users felt it extremely important to prepare for meetings by considering what experiential knowledge to share at the meeting.…”
Section: Factors Related To the Service Usermentioning
confidence: 99%
“…In the research project, researchers, users, staff and service designers have worked together, a partnership which has generated knowledge regarding needs for support that can enable users to participate in their care (Grim, Rosenberg, Svedberg, & Schön, 2016) validated instruments for measuring SDM (Rosenberg, Svedberg, & Schön, 2015; Schön, Svedberg, & Rosenberg, 2015), as well as contributing to the development and validation of a digital interactive decision support tool, DST , for users in psychiatric care (Grim, Rosenberg, Svedberg, & Schön, 2017). The DST is based on the theoretical framework of SDM (Elwyn et al, 2012) and was adapted to the specific needs and preferences of users with mental health problems in a Swedish context (Grim et al, 2016). This article will therefore focus on the process of implementing the DST in six different psychiatric units in Sweden.…”
Section: Introductionmentioning
confidence: 99%
“…Four studies found that more than 60% of participants reported that they had experienced a shared or active approach to decision‐making (Cosh et al, ; De las Cuevas, De Rivera et al, ; Liebherz et al, ; Nott et al, ). However, most studies indicated that SDM was not common (Dahlqvist Jönsson et al, , De las Cuevas & Peñate, , Ehrlich & Dannapfel, , Fukui et al, , Grim et al, , Liebherz, Tlach, Härter, & Dirmaier, , Matthias, Salyers, Rollins, & Frankel, , Salyers et al , Stacey et al, , Souraya et al, , Velligan et al, , Younas et al, ). An observational study showed that consumers felt more involved in the consultation than was observed (Verwijmeren & Grootens, ).…”
Section: Resultsmentioning
confidence: 99%
“…decision‐making capacity, independent living ability, function level, relevant knowledge and interpersonal skills), motivation (influenced by attitudes, trust, locus of control, support networks, previous experience of power, self‐efficacy, self‐confidence and concept of mental illness) and behaviour (such as honesty and openness, respect and politeness, giving feedback, active involvement, history of medication adherence, self‐harm, harm to others and substance use). For instance, many MHPs were concerned that consumers were unable to make decisions because of impaired insight (Ali et al, ; Chong et al, ; Grim et al, ; Shepherd et al, ; Younas et al, ). Consumers identified the necessity of having certain mental health information to engage in decision‐making (Chong et al, ; Dahlqvist Jönsson et al, ; Eliacin et al, , Wright‐Berryman & Cremering ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation